A PRELIMINARY STUDY ON THE USE OF ARABIC TRANSLATION IN HALAL PRODUCT LABELLING BY SMES - Nor Fatini Aqilah Mohamad Soad; Lily Hanefarezan Asbulah; Suhaila Zailani @ Hj. Ahmad, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
In the context of globalization and the increasing demand for halal products, the challenge of producing consistent and culturally appropriate translations emerges as a critical issue in this study. Inaccuracies in translation can lead to errors or misunderstandings about the halal status of products, particularly when specific terms lack direct equivalents in Arabic or when the intended meaning is distorted through translation. Accurate translation is, therefore, essential to ensure compliance with halal standards and to build consumer trust. This study aims to identify the role of Arabic translation in ensuring compliance with halal standards in the labelling of products produced by small and medium enterprises (SMEs). Furthermore, it seeks to analyze the challenges faced by SMEs in ensuring the accuracy of Arabic translations on halal product labels. The study employs a qualitative approach, with a literature review as the primary method. Sources include journals, articles, and documents related to halal labelling and Arabic translation. Data analysis was conducted by examining key themes and concepts related to the use of translations in halal product labelling, providing a comprehensive understanding of the role and challenges faced by SMEs in ensuring the accuracy of Arabic translations on halal product labels. The findings reveal that Arabic translation on halal product labelling plays a vital role in building trust among Muslim consumers and ensuring compliance with international halal standards. However, challenges exist in maintaining translation accuracy and cultural relevance, as well as navigating the variations in halal labelling regulations across international markets. Hence, improvements in standardization and linguistic precision are necessary to support the assurance of halal product status in a more consistent and effective manner.